Generalised network architectures for environmental sensing: case studies for a digitally enabled environment - Mead, Mohammed Iqbal; Bevilacqua, M.; Loiseaux, C.; Hallett, Stephen H.; Jude, Simon; Emmanouilidis, Christos; Harris, Jim A.; Leinster, Paul; Mutnuri, S.; Tran, Trung Hieu; Williams, Leon (Elsevier, 2022)
A digitally enabled environment is a setting which incorporates sensors coupled with reporting and analytics tools for understanding, observing or managing that environment. Large scale data collection and analysis are a part of the emerging digitally enabled approach for the characterisation and understanding of our environment. It is recognised as offering an effective methodology for addressing a range of complex and interrelated social, economic and environmental concerns. The development and construction of the approach requires advances in analytics control linked with a clear definition of the issues pertaining to the interaction between elements of these systems. This paper presents an analysis of selected issues in the field of analytics control. It also discusses areas of progress, and areas in need of further investigation as sensing networks evolve. Three case studies are described to illustrate these points. The first is a physical analytics test kit developed as a part of the “Reinvent the Toilet Challenge” (RTTC) for process control in a range of environments. The second case study is the Cranfield Urban Observatory that builds on elements of the RTTC and is designed to allow users to develop user interfaces to monitor, characterise and compare a variety of environmental and infrastructure systems plus behaviours (e.g., water distribution, power grids). The third is the Data and Analytics Facility for National Infrastructure, a cloud-based high-performance computing cluster, developed to receive, store and present such data to advanced analytical and visualisation tools.
Keywords: Ubiquitous sensor networks; Network analytics; Integrated sensing; Network policy considerations; Living laboratory; Digital environment; Internet of things; Urban observatory